2009
DOI: 10.1111/j.1463-1318.2009.01998.x
|View full text |Cite
|
Sign up to set email alerts
|

Competency in laparoscopic colorectal surgery is achievable with appropriate training but takes time: a comparison of 300 elective resections with anastomosis

Abstract: In this retrospective cohort study we have demonstrate that when matched patients are compared, supervised trainee operating time is significantly longer than that of the consultant trainer but without any significant increase in length of stay, complication or readmission rates. Training to a level of competency takes time but not at the expense of patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
(31 reference statements)
2
17
0
Order By: Relevance
“…Furthermore, the series was unselected to include 'all comers'. We have previously shown no increase in morbidity or mortality in these cases [26], suggesting that in a high-volume centre, senior trainees can gain adequate laparoscopic skills and reach competency relatively quickly.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, the series was unselected to include 'all comers'. We have previously shown no increase in morbidity or mortality in these cases [26], suggesting that in a high-volume centre, senior trainees can gain adequate laparoscopic skills and reach competency relatively quickly.…”
Section: Discussionmentioning
confidence: 66%
“…Borowski et al 12 Chester and Britton 15 Costantino et al 29 Dalton et al 17 Hawkins et al 21 Hilska et al 19 Isbister 13 Khan et al 30 Krishna et al 16 Langhoff et al 23 Li et al 14 Pastor et al 22 Renwick et al 18 Singh and Aitken 25 Tytherleigh et al 24 Verheijen et al 26 Total Heterogeneity:…”
Section: Referencementioning
confidence: 99%
“…Though literature on the influence of trainee involvement on clinical outcomes is mixed, numerous studies have reported increases in operative duration secondary to trainee participation. (710) And recent studies of laparoscopic gastric bypass suggest that differences in the technique used to construct the gastrojejunostomy can have dramatic effects on postoperative outcomes. (11) …”
Section: Introductionmentioning
confidence: 99%